BEBERAPA ASPEK PENGELUARAN KAYU DARI AREAL KONVERSI UNTUK BAHAN BAKU INDUSTRI DI SUMATERASELATAN - lsmatul Hakim; Kirsfianti Linda; Hariyatoo Dwiprabowo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Conversion forests in Indonesia whida are pardy still virgin account for about 41.2 % of the total forest areas. The conversion is needed because of the exlensification of land for fanning, transmigration, and the exlension of urban area. Pre.senJly, the information on wood polential from this forest is scanty. This information is needed to know the possible Ulilization of the logs.The aim of this study is to asses logs potential, and their possible uses for industrial raw malerial and cost analysis. The study was conducted in two forest concession area in South Sumalra Province, in March 1991.The result of this study reveals that the logs potential in the conversion forests are relatively high, especialy of lop wiJh diameler 50 cm and up. It contribults about 60.79 % and 86.99% (from forest concession area I and II) from all logs with diamder 2() Can and up. The dominant tree species found in location are meranti (Shorea sp.), balau (Shorea spp., Hopea spp.), ramin (Gonystylus bancanus Kurz.), kempas (Koompasia malaccensis Maing), jelutung (Dyera spp.) and pulai (Alstonia spp.).The main uses of this wood is for the company own industry uses (57.53%) followed by free sale (28.17 %), and sale to other industry (14.30 %). Logs extraction incurred cost about Rp. 14 450,- until Rp. 16. 700,- per cu.m for forlling, skidding aclivilies and transporting logs to industrial sue.The cost differences depend on wood species, the distances and risk factor. The proportion of this cost is about 19.66 % until 22. 72 % of log price.